A Novel Diagnostic Strategy Using 16α-[18F]-Fluoro-17-β-Estradiol (18F-FES) PET/MRI to Achieve Complete Resection of Intravenous Leiomyomatosis in Reproductive-Age Women. (July 2017) - Chino, Yoko; Tsuyoshi, Hideaki; Tsujikawa, Tetsuya; Okazawa, Hidehiko; Yoshida, Yoshio
Abstract : Abstract: Intravenous leiomyomatosis is a life-threatening leiomyoma that grows into the extrauterine venous system. A high recurrence rate has been reported in reproductive-age women who undergo only tumor excision to preserve fertility. Precise diagnosis of tumor extension is essential to achieve complete resection. A 24-year-old woman presented with hypermenorrhea. Contrast-enhanced MRI showed an intramural myoma with worm-like extension into the right parametrium. 18 F-FES PET/MRI accurately depicted the extension with strong FES activity into the right uterine vein, whereas 18 F-FDG PET/MRI excluded the possibility of malignancy. These modalities can be a novel strategy to manage such cases of intractable intravenous leiomyomatosis.